System architecture for trust-based news recommenders on the web - Briguez, Cristian E. (2011)
A fundamental challenge in personalized news recommendation is to account for the notion of trust. In this work we show how the notion of trust can be qualitatively modeled and incorporated into the architecture of a news recommendation system. The proposed system enables users to express explicit trust statements on news reports, news sources and other users. Trust is modeled and propagated using a dialectical process supported by a defeasible logic programming interpreter. We illustrate the operation of the system with some illustrative examples, describe the system architecture and discuss future steps.